Chemical combinations potentiate human pluripotent stem cell-derived 3D pancreatic progenitor clusters toward functional β cells - Haisong Liu (Nature Portfolio, 2021)
Human pluripotent stem cell (hPSC) derived pancreatic beta cells are a promising and potentially limitless source for cell replacement therapy. Here the authors perform stage-wise chemical screening to develop an improved protocol for hPSC differentiation to functional pancreatic beta cells at high efficiency.